Sodium butyrate restored TRESK current controlling neuronal hyperexcitability in a mouse model of oxaliplatin-induced peripheral neuropathic pain - Idy H.T. Ho; Yidan Zou; Kele Luo; Fenfen Qin; Yanjun Jiang; Qian Li; Tingting Jin; Xinyi Zhang; Huarong Chen; Likai Tan; Lin Zhang; Tony Gin; et al. (Neurotherapeutics)
Chemotherapy-induced peripheral neuropathy (CIPN) and its related pain are common challenges for patients receiving oxaliplatin chemotherapy. Oxaliplatin accumulation in dorsal root ganglion (DRGs) is known to impair gene transcription by epigenetic dysregulation. We hypothesized that sodium butyrate, a pro-resolution short-chain fatty acid, inhibited histone acetylation in DRGs and abolished K+ channel dysregulation-induced neuronal hyperexcitability after oxaliplatin treatment. Mechanical allodynia and cold hyperalgesia of mice receiving an accumulation of 15 ​mg/kg oxaliplatin, with or without intraperitoneal sodium butyrate supplementation, were assessed using von Frey test and acetone evaporation test. Differential expressions of histone deacetylases (HDACs) and pain-related K+ channels were quantified with rt-qPCR and protein assays. Immunofluorescence assays of histone acetylation at H3K9/14 were performed in primary DRG cultures treated with sodium butyrate. Current clamp recording of action potentials and persistent outward current of Twik-related-spinal cord K+ (TRESK) channel were recorded in DRG neurons with small diameters extract. Accompanied by mechanical allodynia and cold hyperalgesia, HDAC1 was upregulated in mice receiving oxaliplatin treatment. Sodium butyrate enhanced global histone acetylation at H3K9/14 in DRG neurons. In vivo sodium butyrate supplementation restored oxaliplatin-induced Kcnj9 and Kcnk18 expression and pain-related behaviors in mice for at least 14 days. Oxaliplatin-induced increase in action potentials frequencies and decrease in magnitudes of KCNK18-related current were reversed in mice receiving sodium butyrate supplementation. This study suggests that sodium butyrate was a useful agent to relieve oxaliplatin-mediated neuropathic pain.